The Comparison of Complication Rates of Subtype Subciliary Approaches: The Review of Literature - Kelahmetoǧlu, O.; Kuzu, I.M.; Ünal, M.; Yaǧmur, C.; Yildiz, K.; Gun̈eren, E. (Ondokuz Mayis University Samsun 55139, 2016)
Incision techniques to lower lid and midface skeleton and their surgical outcomes are often debated in the literature. Our main objective in this study was to discuss the main variations of subciliary approach with their potential complications and to review the literature about the subciliary incision subtypes and their complication rates. We tried to summarize the reported series of patients according to their subciliary approach subtypes and complication rates. A literature search with keywords "subciliary approach" and "subciliary incision" were done and the results were analyzed. All the studies stating information about the variation of subciliary approach and complication rates were included. Although there are many techniques described for approach to lower eyelid and midface skeleton, there are limited amount of studies comparing the complication rates between different approaches. Most of the studies have compared transcutaneous and transconjunctival approaches. Transcutaneous subciliary incision has 3 main modifications: Skin-only, nonstepped skin-muscle and stepped skin-muscle flap. There is only one study found comparing the skin-only and stepped skin-muscle flap series' complications. We included in this review all studies containing the subtype information and complication numbers. Among subciliary incision subtypes the skin-only flap approach has the highest complication rates. According to the literature skin-muscle approaches, either stepped or nonstepped are associated with lower incidence of complications with respect to skin-only flap. They also have more favorable long-term results with almost excellent aesthetic outcomes, decreased ecchymosis and skin necrosis, and significantly lower rates of ectropion. © 2016 OMU.
Keywords: Approach; Ectropion; Lower Lid; Scleral Show; Subciliary